Effect of Information and Communication Technologies (ICTs) on Communication Skills of Agricultural Extension Officials: a case study in Markazi Province of Iran - H. Shabanali Fami,; M . Rezaie,; M. Rahimzadeh,; F. Rostami,; M .Yaghoobi, (Journal of Agricultural Extension Management, 2025)
In Iran, sustainable agriculture and rural development are two pivotal issues in· the national development programmes. Since food security for the citizens is a constitutional principle to which the entire country is committed, the constitution has given strong emphasis to the key preconditions for national food security such as agricultural development, science and technology, environmental protection, social security, poverty alleviation, protection of women's rights and human dignity. The extension system of the country has the responsibility to attain the above objectives